Assessing MANET Routing Protocols: Comparative Analysis of Proactive and Reactive Approaches with NS3 - Ahmed, Khandaker Takdir; Godder, Tapan Kumar; Al Mahmud, Tarek Hasan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
MANETs are dynamic, decentralized networks that employ mobile nodes as hosts and routers. High mobility and frequent topology modifications make routing triky in these networks. This research compares the efficacy of four MANET protocols: DSR, AODV, OLSR, and DSDV. We evaluate various protocols utilizing the NS3 simulator for PDR, throughput, control overhead, and delay. We analyze each protocols strong points and weaknesses under varied node densities, pause durations, and network sizes. DSR has the greatest PDR and lowest control overhead, making it ideal for dynamic networks. OLSR maintains high throughput and short delay despite increasing control overhead. DSDV has the maximum throughput but significant control overhead and PDR in bigger networks. AODV performs well in smaller networks but degrades significantly as network size rises. This research illuminates MANET routing protocol trade-offs, helping to build more resilient and efficient communication techniques for diverse application situations. Our results imply that DSR is best for dynamic contexts and OLSR for route availability and low latency.